eLIFEwithIBD: study protocol for a randomized controlled trial of an online acceptance and commitment therapy and compassion-based intervention in inflammatory bowel disease - Ferreira, Cláudia; Pereira, Joana; Matos-Pina, Inês; Skvarc, David; Galhardo, Ana; Ferreira, Nuno; Carvalho, Sérgio A.; Lucena-Santos, Paola; Rocha, Bárbara S.; Oliveira, Sara; Portela, Francisco; Trindade, Inês A. (Frontiers in Psychology, 2024)
Background: Inflammatory bowel disease (IBD) entails physical, psychological, and social burden and holds a significant impact on quality of life. Experiential avoidance, cognitive fusion, shame, and selfcriticism have been identified as possible therapeutic targets for improving mental health in people with IBD. Traditional face-to-face psychological therapy continues to provide obstacles for patients seeking assistance. Online psychological therapies centered on acceptance, mindfulness, and compassion have been shown to improve psychological distress in other populations.Objective: This paper presents the study protocol of a two-arm Randomized Controlled Trial (RCT) of an ACT and compassion-based, online intervention -eLIFEwithIBD -on the improvement of psychological distress, quality of life, work and social functioning, IBD symptom perception, illness-related shame, psychological flexibility, and self-compassion.The eLIFEwithIBD intervention is an adaptation of the LIFEwithIBD programme (delivered through an in-person group format) and entails an ACT, mindfulness, and compassion-based intervention designed to be delivered as an e-health tool for people with IBD. This protocol outlines the structure and contents of the eLIFEwithIBD intervention. Participants were recruited by an advertisement on the social media platforms of Portuguese Associations for IBD in January 2022. A psychologist conducted a brief interview with 80 patients who were interested in participating. Fifty-five participants were selected and randomly assigned to one of two conditions [experimental group (eLIFEwithIBD + medical TAU; n = 37) or control group (medical TAU; n = 18)]. Outcome measurement took place at baseline, post-intervention, and 4-month follow-up. All analyses are planned as intent-to-treat (ITT).The eLIFEwithIBD intervention is expected to empower people with IBD by fostering psychological strategies that promote illness adjustment and well-being and prevent subsequent distress.The eLIFEwithIBD aims to gain a novel and better understanding of the role of online contextual behavioral interventions on improving the quality of life and mental health of people with IBD.